Low glycemic index rice: a healthier diet for countering diabetes epidemic in Asia - Tiozon, Rhowell Jr; Lenaerts, Bert; Kor, Sakshi; Demont, Matty; Fernie, Alisdair; Sreenivasulu, Nese (Elsevier, 2025)
The prevalence of type 2 diabetes is rising worldwide, particularly in Asia, where rice is a dietary staple. Hence, it is essential to consume low glycemic index (GI) food. Here, we review the potential of low GI and high resistant starch (RS) of rice to mitigate diabetes risk. Progress has been made in lowering the GI of rice without compromising yield and grain quality through marker-assisted breeding techniques. To enhance RS content, mutation breeding and genome editing were used. Deployment of these new varieties in global food systems remains critical through policy initiatives such as ‘Seeds without Borders’ and the widespread deregulation of genome editing plants that can expedite the wider adoption of low-GI and high-RS rice.